1998
DOI: 10.1073/pnas.95.25.15020
|View full text |Cite
|
Sign up to set email alerts
|

Rolipram, a type IV-specific phosphodiesterase inhibitor, facilitates the establishment of long-lasting long-term potentiation and improves memory

Abstract: In an attempt to improve behavioral memory, we devised a strategy to amplify the signal-to-noise ratio of the cAMP pathway, which plays a central role in hippocampal synaptic plasticity and behavioral memory. Multiple highfrequency trains of electrical stimulation induce long-lasting long-term potentiation, a form of synaptic strengthening in hippocampus that is greater in both magnitude and persistence than the short-lasting long-term potentiation generated by a single tetanic train. Studies using pharmacolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
325
2
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(362 citation statements)
references
References 39 publications
34
325
2
1
Order By: Relevance
“…While overall inhibition of PDE4 enhances memory performance in animals (Barad et al, 1998;Zhang et al, 2004Zhang et al, , 2005, PDE4BÀ/À mice did not show significant changes in either short-or long-term memory in step-down passive avoidance and Morris water-maze tasks (Table 1 and Figure 5), two tests measuring hippocampus-based memory (Bevilaqua et al, 1997). This is consistent with the limited expression of PDE4B in the hippocampus (Cherry and Davis, 1999).…”
Section: Pde4b-deficiency and Behavior H-t Zhang Et Alsupporting
confidence: 75%
See 2 more Smart Citations
“…While overall inhibition of PDE4 enhances memory performance in animals (Barad et al, 1998;Zhang et al, 2004Zhang et al, , 2005, PDE4BÀ/À mice did not show significant changes in either short-or long-term memory in step-down passive avoidance and Morris water-maze tasks (Table 1 and Figure 5), two tests measuring hippocampus-based memory (Bevilaqua et al, 1997). This is consistent with the limited expression of PDE4B in the hippocampus (Cherry and Davis, 1999).…”
Section: Pde4b-deficiency and Behavior H-t Zhang Et Alsupporting
confidence: 75%
“…It is well established that PDE4 inhibitors such as rolipram produce antidepressant-like and memory-enhancing effects (Barad et al, 1998;O'Donnell and Zhang, 2004;Zhang et al, 2004Zhang et al, , 2006Zhang and O'Donnell, 2007). They also may induce anxiogenic-like effects and sedation (Heaslip and Evans, 1995;Imaizumi et al, 1994;Silvestre et al, 1999b), although an anxiolytic-like effect also has been reported (Silvestre et al, 1999a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rolipram also enhances memory (Barad et al, 1998;Bourtchouladze et al, 2003;Zhang et al, 2004). This, coupled with the effect of rolipram on PPI, suggests that cAMP PDE inhibitors may prove successful in treating the debilitating cognitive deficits that are associated with schizophrenia.…”
Section: Discussionmentioning
confidence: 92%
“…In the uninjured CNS, rolipram increases cAMP levels in the hippocampus (Barad et al, 1998, Van Staveren et al, 2001, Giorgi et al, 2004, and specifically in microglia and astrocytes as compared to neurons (Zhang et al, 2002). There are also very modest increases in cGMP levels with high concentrations of rolipram, suggesting that rolipram could work through cGMP although this is more unlikely (Van Staveren et al, 2001).…”
Section: Discussionmentioning
confidence: 99%